2014
DOI: 10.1097/ico.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Descemet Membrane Detachment After Nd

Abstract: To our knowledge, this is the first reported case of DMD after Nd:YAG laser capsulotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…11 As one of the rare complications of laser capsulotomy in a patient with FECD, Afriat et al reported a Descemet membrane detachment in a 89-yearold man 1 day after YAG-PC laser capsulotomy. 12 The aim of this prospective case-control study was to investigate the influences of YAG-PC on corneal endothelium, central corneal thickness, and IOL position in pseudophakic eyes with FECD and posterior capsular opacification.…”
Section: Introductionmentioning
confidence: 99%
“…11 As one of the rare complications of laser capsulotomy in a patient with FECD, Afriat et al reported a Descemet membrane detachment in a 89-yearold man 1 day after YAG-PC laser capsulotomy. 12 The aim of this prospective case-control study was to investigate the influences of YAG-PC on corneal endothelium, central corneal thickness, and IOL position in pseudophakic eyes with FECD and posterior capsular opacification.…”
Section: Introductionmentioning
confidence: 99%